2005
DOI: 10.1037/0022-006x.73.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Equivalence of the Center for Epidemiological Studies Depression Scale for Latino and Anglo Adolescents: A National Study.

Abstract: The cross-ethnic measurement equivalence of the Center for Epidemiologic Studies Depression Scale (CES-D; L. S. Radloff, 1977) was examined using a subsample of adolescents (N=10,691) from the National Longitudinal Study of Adolescent Health. Configural and metric invariance, as well as functional and scalar equivalence, were examined for Anglo American, Mexican American, Cuban American, and Puerto Rican American youths age 12-18 years. Confirmatory factor analysis (CFA) in each group provided evidence of conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
214
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 231 publications
(234 citation statements)
references
References 48 publications
(81 reference statements)
14
214
2
1
Order By: Relevance
“…Responses were on a 4-point scale ranging from 0 (never or rarely) to 3 (most of the time or all of the time). The 20 items are similar to items on Radloff's (1977) Center for Epidemiological Studies-Depression Scale (Crockett, Randall, Shen, Russell, & Driscoll, 2004;Udry, 2001). On 18 of the items, participants were asked how true each item was during the past week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses were on a 4-point scale ranging from 0 (never or rarely) to 3 (most of the time or all of the time). The 20 items are similar to items on Radloff's (1977) Center for Epidemiological Studies-Depression Scale (Crockett, Randall, Shen, Russell, & Driscoll, 2004;Udry, 2001). On 18 of the items, participants were asked how true each item was during the past week.…”
Section: Methodsmentioning
confidence: 99%
“…Because African American same-sex-attracted male youths report higher levels of depression than African American other-sex-attracted male youths regardless of whether multiracial youths are included, we did not feel this difference added any more information. 5 Crockett et al (2004) addressed the concern regarding the two different time frames for this measure of depression. They conducted factor analyses on the items and found that the factor loadings for the 2 items with the year time frame did not differ from the other 18 items.…”
Section: Methodsmentioning
confidence: 99%
“…At the most basic level, there may be a lack of construct equivalence, such that each group conceptualizes parental support differently (Crockett, Randall, Shen, Russell, & Driscoll, 2005;Hui & Triandis, 1985). If so, a measure of parental support developed for one group (e.g., European Americans) would fail to capture relevant aspects of support as understood by the other group (e.g., Filipino Americans).…”
Section: How Similar Are Measures Across Ethnic Groups?mentioning
confidence: 99%
“…We focused on one subgroup of Latinos (Mexican Americans), because prior research has revealed differences between Latino subgroups on multiple dimensions, including cultural traditions, historical experiences, and demographic characteristics (e.g., Baca Zinn, 1995), as well as depressive symptoms and syndromes (e.g., Crockett, Randall, Shen, Russell, & Driscoll, 2005). on the basis of theory and empirical research, we predicted that acculturative stress would be associated with higher levels of depressive and anxiety symptoms.…”
Section: The Present Studymentioning
confidence: 99%